Characterisation of Nav1.7 functional expression in rat dorsal root ganglia neurons by using an electrical field stimulation assay. Issue 1 (November 2017) - Fouillet, Antoine; Watson, Jake F.; Piekarz, Andrew D.; Huang, Xiaofang; Li, Baolin; Priest, Birgit; Nisenbaum, Eric; Sher, Emanuele; Ursu, Daniel
Background: The Nav 1.7 subtype of voltage-gated sodium channels is specifically expressed in sensory and sympathetic ganglia neurons where it plays an important role in the generation and transmission of information related to pain sensation. Human loss or gain-of-function mutations in the gene encoding Nav 1.7 channels (SCN9A) are associated with either absence of pain, as reported for congenital insensitivity to pain, or with exacerbation of pain, as reported for primary erythromelalgia and paroxysmal extreme pain disorder. Based on this important human genetic evidence, numerous drug discovery efforts are ongoing in search for Nav1.7 blockers as a novel therapeutic strategy to treat pain conditions. Results: We are reporting here a novel approach to study Nav 1.7 function in cultured rat sensory neurons. We used live cell imaging combined with electrical field stimulation to evoke and record action potential-driven calcium transients in the neurons. We have shown that the tarantula venom peptide Protoxin-II, a known Nav 1.7 subtype selective blocker, inhibited electrical field stimulation-evoked calcium responses in dorsal root ganglia neurons with an IC50 of 72 nM, while it had no activity in embryonic hippocampal neurons. The results obtained in the live cell imaging assay were supported by patch-clamp studies as well as by quantitative PCR and Western blotting experiments that confirmed the presence of Nav 1.7 mRNA and protein in dorsal root ganglia but not in embryonic hippocampal neurons. Conclusions: The findings presented here point to a selective effect of Protoxin-II in sensory neurons and helped to validate a new method for investigating and comparing Nav 1.7 pharmacology in sensory versus central nervous system neurons. This will help in the characterisation of the selectivity of novel Nav 1.7 modulators using native ion channels and will provide the basis for the development of higher throughput models for enabling pain-relevant phenotypic screening.